3D scene and geological modeling using integrated multi-source spatial data: Methodology, challenges, and suggestions. (June 2020) - Pan, Dongdong; Xu, Zhenhao; Lu, Xinming; Zhou, Longquan; Li, Haiyan
Highlights: An integrated modeling method of multi-source complex spatial data is proposed. 3D scene modeling of a deep buried mine site is constructed. 3D geological modelling of an open pit is constructed. Significance, technical challenge, and suggestion for geological modeling is proposed. Abstract: The visualization and analysis of massive, multi-source, multi-dimensional, heterogeneous, dynamic, and complex spatial data is playing an increasingly important role in 3D scene and geological modeling. There are great differences in various research fields regarding data acquisition techniques, morphological descriptions, and application purposes of spatial objects. Therefore, based on an existing three-dimensional visualization technology and analysis program of spatial data, an integrated processing method for the effective fusion and analysis of multi-source complex spatial data is proposed. This method combines a massive point cloud model with a digital elevation model, in addition to combining the complex stratum with fault modeling technology. The structural grid and geological grid are effectively combined to realize the unified modeling and visualization of natural and artificial objects. This method was then applied to a 3D modeling scene of deeply buried mines and a geological construction model for open pit mines. The comprehensive and effective utilization of multi-source geological data is realized by using this modeling method. Finally, the challenges of spatial data visualization from the aspects of the difficulties in spatial data acquisition, the complexities of the spatial structure, the constraint relations of geological bodies, and the complexity of the 3D modeling process are discussed in this study. Three specific suggestions are proposed. This study enhances the application efficiency of multi-source spatial data modeling technologies already in practice and provides reference for future applications and developments.